Balance Strategies of Production Logistics Based on Flexible Production (Asian Business Research, 2018)
Flexible production is implemented effectively on the condition that production logistics is kept in balance. The paper starts with the analyses of the balanced factors of logistics for flexible production, then, furthers to discuss how to balance production logistics. The conclusion can be drawn that the improvement of the load rate, balance rate of the production, and the executive rate of the contract is the purpose of balance logistics for flexible production and the main contents of logistics balance while keeping the balance of production line, identifying bottlenecks resources, compiling production planning and setting buffer links are the key means and effective measures of balancing production logistics.